STUDENTS’ LIVED EXPERIENCE OF LEARNING ENGLISH THROUGHT TEAM GAMES TOURNAMENT AT THE TENTS GRADE OF SMK NEGERI 1 SIANTAR - Thesa Laora Miranda Siahaan; Deswita Fitriani Samosir; Heltri Fildayanti Samongilailai; Dumaris Silalahi (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
Previous research on Teams Games Tournament (TGT) has been dominated by a quantitative focus on learning outcomes, creating a gap in understanding the affective and psychosocial aspects of learning. This qualitative phenomenological study aims to describe the lived experiences of tenth-grade students at SMK Negeri 1 Siantar in learning English through the TGT model. Through phenomenological interviews with 35 students, this study identified five essential themes: (1) Motivation and Learning Enjoyment, (2) Teamwork and Sense of Connectedness, (3) Competition and Emotional Pressure, (4) Independence and Self-Reflection, and (5) Meaningful Learning. The findings reveal that the dynamics of TGT effectively fulfill the Three Basic Psychological Needs in Self-Determination Theory (SDT): Relatedness, Competence, and Autonomy. Overall, students perceive TGT as a “living” and meaningful learning experience, as it integrates academic aspects with the development of soft skills such as collaboration and confidence.